Outcomes After Primary Infliximab Treatment Failure in Inflammatory Bowel Disease. Issue 7 (July 2017) - Buhl, Sine; Steenholdt, Casper; Rasmussen, Maria; Borghede, Märta K.; Brynskov, Jørn; Thomsen, Ole Ø.; Ainsworth, Mark A.
Abstract : Background: Primary infliximab treatment failure is common in patients with inflammatory bowel disease and represents a challenge to clinicians. Treatment options are limited. This study assessed the prognosis, defined as surgery-free survival, in patients with primary infliximab treatment failure as compared to patients without primary failure (initial responders). Furthermore, this study assessed the specter of medical therapies used after primary infliximab treatment failure along with treatment outcomes. Methods: Retrospective, observational, cohort study of patients with inflammatory bowel disease treated with infliximab as first-line anti–tumor necrosis factor treatment at a tertiary center. Primary infliximab treatment failure was defined as no clinical improvement during infliximab induction therapy resulting in discontinuation of infliximab therapy. Results: A total of 560 patients (Crohn's disease n = 353 and ulcerative colitis n = 207) were treated with infliximab. Among these, 81 (15%) had primary infliximab treatment failure after a median of 3 infusions (weeks 0, 2, and 6) (interquartile range 2–4). The median surgery-free survival was 196 days from first infusion. One year after primary infliximab treatment failure, the majority of patients (n = 51, 63%) had inflammatory bowel disease–related surgery (Crohn's disease n = 19, 58%; ulcerative colitis n = 32, 67%; P = 0.49). There was a markedly increased risk of surgery in patients with primary infliximab treatment failure as compared to initial responders: odds ratio 6.3 (3.8–10.6), P < 0.0001. Among 30 patients handled by medical therapies, 16 (53%) still had active disease 1 year after primary infliximab treatment failure. Conclusions: Primary infliximab treatment failure is associated with poor outcome including high risk of surgery or sustained active disease despite medical interventions. Abstract : Article first published online 25 April 2017.